2006
DOI: 10.1111/j.1365-2141.2006.06198.x
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein promotes platelet adhesion to endothelial cells: a potential pathway in atherothrombosis

Abstract: SummaryC-reactive protein (CRP) is a strong predictor for acute cardiovascular events. Several endothelial prothrombotic effects of CRP have been recently reported. This study examined the effect of CRP on bovine aortic endothelial cell (EC) activation and capacity to recruit human platelets under flow conditions using the cone and plate(let) analyser method. Human recombinant CRP promoted platelet adhesion in a dose-and timedependent manner, with a maximal effect at 20 lg/ml (increase of 174% over baseline, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 35 publications
1
40
2
Order By: Relevance
“…CRP has been reported as a potent peptide that causes platelet adhesion to epithelial cells, thereby regulating atherothrombosis (39). This step is also regulated by vitronectin and its receptor, since they interact with thrombin and antithrombin III (40).…”
Section: Discussionmentioning
confidence: 99%
“…CRP has been reported as a potent peptide that causes platelet adhesion to epithelial cells, thereby regulating atherothrombosis (39). This step is also regulated by vitronectin and its receptor, since they interact with thrombin and antithrombin III (40).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that PKC activation and PKC-dependent MAPK activation are major participants in the regulation of macrophage LPL (19,20,22,23). Although indirect evidence has been provided for a role of PKC in CRP-induced platelet adhesion and VCAM-1 expression (41,42), the levels of PKC activity in CRP-treated vascular cells has not yet been documented. In the present study, we demonstrated that CRP increases the expression of conventional PKC isoforms in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet adhesion to MHECs from CRPtg or wild-type mice and to human umbilical vein endothelial cells (HUVECs) was studied using the CPA, as previously described (39). Forty thousand MHECs or HUVECs at passage 2 to 3 were plated on four-well plates.…”
Section: Methodsmentioning
confidence: 99%